A brief review and evaluation of non-thermal chemical flooding for enhanced oil recovery - Chen, Chong Chung; Jidon @ Adrian Janaun; Abdul Karim Mirasa; Abu Zahrim Yaser (UniSE Press, 2021)
Non-thermal chemical flooding is unique to conventional enhanced oil recovery of using water flooding. This paper investigated non-thermal chemical flooding based on some basic characteristics and theoretical understandings derived from non-thermal chemical EOR methods. Fundamental interfacial tension properties, capillary effects, adsorption behaviors, and the types of non-thermal chemicals such as alkaline, surfactant, and polymers involved in the current enhanced oil recovery techniques.